Ocular alterations in dogs naturally infected by Leishmania (Leishmania) chagasi - Brito, F. L. C.; Alves, L. C.; Maia, F. C. L.; Santos, E. S. C.; Laus, J. L.; Meunier, I. M. J. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2006)
Ocular conditions, anti-Leishmania antibodies and total protein of the aqueous humor were studied in dogs naturally infected by Leishmania ( Leishmania) chagasi. Fifty dogs were analyzed and assigned into two groups of 25 animals each. All animals were submitted to routine ophthalmic exam. Results showed that 76% of the affected animals presented ocular signs, being uveitis the predominant. The mean of total protein in the aqueous humor of animals with uveitis was higher ( P < 0.05) when compared to the mean of animals with other ocular signs or no clinical sign. The anti- Leishmania chagasi antibody values in plasma were superior to those found in the aqueous humor (P < 0.05).
Keywords: dog; Leishmania ( Leishmania) chagasi; aqueous humor; antibodies; protein